DEVELOPMENT AND CHARACTERIZATION OF BIODEGRADABLE FILMS FROM MACÁÇAR BEAN STARCH (VIGNA UNGUICULATA (L.) WAP) (Editora Impacto Científico, 2025)
The present work is related to the preparation and characterization of biodegradable flexible films from macáçar bean starch, plasticized with glycerol and the glycerol and glacial acetic acid (HAc) mixture. The films were obtained by casting using macáçar bean starch (3 g/100 g of film-forming solution) and different concentrations of the glycerol plasticizing agent (20 g and 30 g/100 g of starch) and the glycerol and glacial acetic acid mixture, in the proportions 20 g and 10 g/100 g of film-forming solution, respectively. The films presented good continuity, uniformity, handling, transparency and, also, absence of bubbles and cracks on the surface. The increase in the amount of film- forming solution in the formulations, from 0.23 to 0.46 g/cm2, positively affected the thickness, weight and density, but did not alter the moisture and transparency of the films. The hydrophilic character of films increased with the addition of plasticizing agent.DOI: https://doi.org/10.56238/edimpacto2025.090-017